Differential Glucocorticoid Receptor‐Mediated Effects on Immunomodulatory Gene Expression by Progestin Contraceptives: Implications for HIV‐1 Pathogenesis. (18th February 2014) - Hapgood, Janet P.; Ray, Roslyn M.; Govender, Yashini; Avenant, Chanel; Tomasicchio, Michele
<x xml:space="preserve">Abstract</x> Whether hormonal contraceptives increase HIV‐1 acquisition, transmission and disease progression are critical questions. Clinical research has been hampered by a lack of understanding that different progestins used in contraception exhibit differential off‐target effects via steroid receptors other than the progesterone receptor. Of particular, relevance is the relative effects of medroxyprogesterone acetate (MPA) and norethisterone enanthate (NET‐EN), widely used as injectable contraceptives in sub‐Saharan Africa. While most high‐quality clinical studies find no increased risk for HIV‐1 acquisition with oral contraception or injectable NET‐EN, most do find an increase with MPA, particularly in young women. Furthermore, mounting evidence from animal, ex vivo and biochemical studies are consistent with MPA acting to increase HIV‐1 acquisition and pathogenesis, via mechanisms involving glucocorticoid‐like effects on gene expression, in particular genes involved in immune function. We report that MPA, unlike NET and progesterone, represses inflammatory genes in human PBMCs in a dose‐dependent manner, via the glucocorticoid receptor (GR), at concentrations within the physiologically relevant range. These and published results collectively suggest that the differential GR activity of MPA versus NET may be a mechanism whereby MPA, unlike NET or progesterone, differentially modulates HIV‐1 acquisition and pathogenesis in target cells where the GR is the predominant steroid receptor expressed.